Letter - Tomás, Pascual, 1893-1972
026-0052-001 Pascual Tomas Député 69, Rue du Taur TOULOUSE. France. Strictly Private + Confidential Toulouse the 4th of July 1939. Sir Walter Citrine London. Very Dear Friend, Just received to-day a letter from my wife, in which she tells me the economic difficulties where she found herself at the present time and the impossibility to attend our daughter suffering from a tuberculosis located in the arm. All we had in our house has been taken away by the nationalists, even the dresses from my daughters and wife. I received a few days ago a small amount of money from the International Metalurgist as a present, to help me to live in better conditions. I would like to change this amount in pesetas and send it to my wife to avoid their starving. From Toulouse there is no means for me to send the money with security. For this purpose I beg you to tell me if by the officials ways it would be possible to reach my wife and give her in proper hands the amount I will send you. I am asking you very dear Citrine to do all what you can to secure my daughters and wife get away from the hell where they are living and help me for the present to send them the money and foods that they need very badly. Yours very truly friend. P. Tomàs 292/946/26/52